OPTIMALISATION OF THE BLADE MOVEMENT OF THE MOWER - Jozef ŠKRABALA; Adrián HAJDUČÍK; Štefan MEDVECKÝ; František BRUMERČÍK (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents the correct adjustment of the mower’s blade movement relative to the forward movement of the mower. Everywhere around us are gardens, parks and meadow, which gives us reason to solve issues with mowing. The first part of this article shows agricultural machines, which are used today and the principle of correct cut of grass stalks. The next part shows the method of adjusting the mower’s blade speed. Design of a simple model was done with the use of Solid Edge Premium CAD. For computation, MSC Adams was used and post-processing was done with the use of Matlab. The connection between MSC Adams and Matlab was created by co-simulation.